OBSTACLES TO IMPLEMENTATION AND STRATEGY FORMULATION MANAGEMENT STRATEGY IN BUSINESS AND ISSUES OF ITS FORMATION - Dedajanov Bahtiyor Nabijanovich; Mirzababaev Abdullo Mamasodikjonovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article describes the factors of business management, the content of management strategies, scientific approaches. The problems and obstacles identified as a result of research in business activities have been identified. Also, the expression and analysis of business strategies in the economy of Namangan region as a result of indicators, recommendations for solving existing problems are developed.